The full-length E6 protein of human papillomavirus type 16 has transforming and trans-activating activities and cooperates with E7 to immortalize keratinocytes in culture. - Sedman, S A (1991)
The wild-type E6 and E7 genes of human papillomavirus type 16 (HPV16) can cooperate to immortalize normal human keratinocytes in culture. The E6 open reading frame of HPV16 and other HPV types highly associated with cervical cancer has the potential of encoding both full-length E6 and two truncated E6* proteins, the latter being generated via splicing within the E6 open reading frame portion of the E6-E7 polycistronic transcript. Those types, such as HPV6, that are infrequently associated with cervical carcinoma lack the splice site and encode only a full-length E6. We have now found that, in addition to cooperating with E7 to immortalize keratinocytes, HPV16 E6 can induce anchorage-independent growth in NIH 3T3 cells and trans-activate the adenovirus E2 promoter. HPV6 E6 was also able to trans-activate the adenovirus E2 promoter, although it was inactive in both cell transformation assays. An HPV16 splice site mutant which expressed only the full-length HPV16 E6 was active in all three assays, indicating that the E6* proteins are not required for these activities. The plasmid which encodes the E6* proteins was inactive and did not potentiate the activity of the HPV16 splice site mutant. The mutation that prevented splicing in E6-E7 mRNA severely reduced the level of E7 protein and increased E6 protein. Taken together, the results suggest that the primary function of the splice within E6 is to facilitate the translation of E7 and reduce translation of full-length E6, rather than to generate biologically active E6* proteins.